Large Subcapsular Splenic Hematoma with a Large Pancreatic Pseudocyst Was Successfully Treated with Splenic Arterial Embolization and Ultrasound-Guided Percutaneous Drainage of Pancreatic Pseudocyst - Song Zhang; Fei Liu; Heena Buch; Guifang Xu; Lei Wang (Case Reports in Medicine)
Subcapsular splenic hematoma is a rare complication of pancreatitis. The management for subcapsular splenic hematoma remains controversial. We herein report a case of a large subcapsular splenic hematoma with a large pancreatic pseudocyst, which was successfully treated with splenic arterial embolization and ultrasound- (US-) guided percutaneous drainage of pancreatic pseudocyst, for the first time. A 44-year-old male suffered from recurrent abdominal pain for more than two years. He had previous 3 episodes of pancreatitis. A subcapsular splenic hematoma (16.0 × 16.0 × 7.6 cm) with pancreatic pseudocyst (13.5 × 10.0 × 8.0 cm) was shown on abdominal computed tomography (CT). He underwent splenic arterial embolization to decrease the blood supply of the spleen and then ultrasound-guided percutaneous drainage of the large pancreatic pseudocyst. After 2 weeks, the repeated CT-Abdomen showed the disappearance of pancreatic pseudocyst and multiple areas of infarction on the spleen, while the splenic subcapsular hematoma had also significantly reduced. The patient was discharged after almost a month of his hospital admission with the drainage tube attached, and about 2 weeks later the drainage tube was removed upon CT scan confirmation of decrease in the volume of the subcapsular hematoma. Patient had no abdominal symptoms at the 1.5-year follow-up.